Critical Time Intervention for Homeless People Making the Transition to Community Living: A Randomized Controlled Trial. Issue 1 (5th September 2017) - de Vet, Renée; Beijersbergen, Mariëlle D.; Jonker, Irene E.; Lako, Danielle A.M.; van Hemert, Albert M.; Herman, Daniel B.; Wolf, Judith R.L.M.
Highlights: This study contributes to a European evidence base for effective interventions for homeless people. It is the first RCT conducted in Dutch shelter services; this is uncommon outside the United States. In this sample, recurrent homelessness was rare 9 months after moving from a shelter to housing. Beneficial effects of CTI on mental health seem to be independent of health care system or context. Abstract: To help create an evidence base in Europe for effective interventions that improve the well‐being of homeless people, we tested whether critical time intervention (CTI), a time‐limited intervention developed to support vulnerable people during times of transition, is effective outside the United States. For this multicenter, parallel‐group randomized controlled trial, 183 adults who were moving from shelters in the Netherlands to supported or independent housing were allocated to CTI or care‐as‐usual. The primary outcome was number of days rehoused, which was assessed by interviewing participants four times during a 9‐month follow‐up. Outcomes were analyzed with three‐level mixed‐effects models. The primary outcome did not differ between groups. CTI had a significant effect on family support and, for people experiencing less social support, psychological distress. Groups did not differ significantly on social support, fulfillment of care needs, quality of life, self‐esteem, excessive alcohol use, or cannabis use. Because few participants were homeless at 9 months, more research is needed to establish whether CTI can prevent long‐term recurrent homelessness. Given recent emphasis on informal support in public services and positive effects of CTI on family support and psychological distress, CTI is a fitting intervention for Dutch shelter services.